The Toy Department Has Grown Up: The 2021 International Sports Press Survey (ISPS) in Comparison to the 2011 Survey - Thomas Horky; Joerg-Uwe Nieland; Christof Seeger (Journalism and Media, 2025)
Sport and sports communication is growing. Sport is an integral part of (everyday) communication in both traditional and so-called new media. Digitalization poses major challenges for sports journalism. In connection with the changing media consumption, the crisis of the majority of print media and the increasing globalization and standardization of sports at the international level, this applies above all to daily newspapers. In addition, sports newsrooms have been described as “toy departments”. This paper discusses the findings of the 2021 International Sports Press Survey (ISPS) on the current state of the quality of sports reporting in daily newspaper and confronts these findings with the results of the 2011 study. Against the backdrop of quality journalism based on diversity, the quantitative content analysis examines 6614 articles from eight countries. The 2021 ISPS results highlighted several key findings regarding the quality and diversity of sports journalism. These included the persistent underrepresentation of women as both authors and protagonists in sports reporting, a focus on current events over in-depth research, and a limited use of sources. However, when compared to data from a decade ago, there is evidence of a slight positive trend towards increased diversity and improved quality in sports journalism.